Level of Dependency Based on Barthel and Lawton Score in Older People Living in Panti Werdha, Ciparay - Rizky Nurwan Diyanto; Marina A. Moeliono; Lazuardhi Dwipa (Althea Medical Journal, 2016)
Background: The population of older people continues to increase. Thus, many kinds of health-related problems can occur, such as a decrease independence level in performing activities of daily living (ADL) which can be assessed by using Barthel and Lawton index. Barthel index assesses basic ADL such as mobility function, continence, and self-care. Lawton index assesses instumental ADL that are a person’s ability to use tools and face other people. There are no data available reflecting the dependency of the older people at Panti Werdha, Ciparay . This study aimed to observe the level of dependence of the older people in Panti Werdha using Barthel and Lawton index.Methods: This study was a descriptive study and was conducted at Panti Werdha, Ciparay from September to November 2015 using the total population. The level of dependence in the older people was assessed by Barthel and Lawton index. Barthel index was divided into independent, mild dependent, moderate dependent, severe dependent, and totally dependent. Lawton index was divided into independent, low dependent, high dependent, and totally dependent.Results: A total of 144 older people participated as respondents in this study. Based on the Barthel index score, it showed that 51.4% of the subjects were dependent. As for the Lawton index scor¬¬e, it showed that 81.2% of the subjects were dependent.Conclusions: Most of the older people in Panti Werdha, Ciparay are categorized as dependent, where they will need help in performing basic and instrumental ADL. [AMJ.2016;3(4):493–8] DOI: 10.15850/amj.v3n4.929